2012
DOI: 10.1088/0957-4484/23/4/045104
|View full text |Cite
|
Sign up to set email alerts
|

EGF-functionalized single-walled carbon nanotubes for targeting delivery of etoposide

Abstract: To enhance the therapeutic potential of etoposide (ETO), we devised a targeted drug delivery system (TDDS) of epidermal growth factor-chitosan-carboxyl single-walled carbon nanotubes-ETO (EGF/CHI/SWNT-COOHs/ETO) using modified SWNTs (m-SWNTs) as the carrier, EGF-functionalized SWNTs (f-SWNTs) as the targeted moiety and ETO as the drug. After SWNT-COOHs were conjugated with CHI (CHI/SWNT-COOHs/ETO), they displayed high solubility and stable dispersion in aqueous solution. The drug loading capacity was approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…It is propitious for S-D1@L-D2 NPs to transport through blood vessels and retain in circulation for long periods, as well as internalize by means of endocytosis. 25,37,38 Its inner smaller…”
Section: Physical and Chemical Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…It is propitious for S-D1@L-D2 NPs to transport through blood vessels and retain in circulation for long periods, as well as internalize by means of endocytosis. 25,37,38 Its inner smaller…”
Section: Physical and Chemical Characterizationmentioning
confidence: 99%
“…Therefore, the intracellular precision release of NDDS-loaded P-gp substrates is still a demanding issue. There were a variety of drug delivery techniques to reduce the efflux associated with P-gp, such as using biological materials with interference of P-gp function, like vitamin E d-a-tocopheryl polyethylene glycol 1000 succinate (TPGS), and adding P-gp inhibitor, [24][25][26][27] like verapamil. Recently, we have reported that a type of NPs can carry a drug as the P-gp substrate into the nucleus and release it in the nucleus of MDR cell.…”
Section: Introductionmentioning
confidence: 99%
“…61 Its drug loading capacity was 25−27%. The cell death induced by the EGF/CHI/SWNT−COOHs/ ETO was as much as 2.7 times that due to ETO alone.…”
Section: Organo-modified Cntsmentioning
confidence: 99%
“…Both theoretical and experimental works (Burgess et al, 2003;Dawson et al, 2005;Ferguson et al, 2003) have shown a high binding affinity of EGF towards the EGFR, while a kinetic study of the EGF-EGFR interaction suggested that EGF can bind with either an inactive expanded EGFR dimer or a tethered EGFR monomer before inducing the EGFR dimerization process (Björkelund, Gedda, Malmqvist, & Andersson, 2013;Lemmon, 2009 in vitro and in vivo studies on the use of EGF as targeting agent in DDS applications (Bhirde, et al, 2009;Cheng et al, 2012;Shevtsov et al, 2014;Tseng et al, 2008;Yang et al, 2009). Therefore, we aimed to investigate the structure and dynamics properties as well as the proteinprotein binding efficiency of EGFR•EGF-CS-SWCNT-Drug complex in comparison to that for the EGFR•EGF complex and individual EGFR protein by using molecular dynamics simulations (MDSs).…”
Section: Introductionmentioning
confidence: 99%